Exemplar in the coverage of the Bangsamoro framework agreement using computational tools to compare Qatari and Philippine news framing - Cabling, Mark L.; Drago, Fabrizio; Andrei, Amanda T. (2017)
On 7 October 2012, the Philippine Government and the Moro Islamic Liberation Front agreed to the framework of a peace deal (signed on 15 October 2012) with the aim to pave the way for enduring peace between the two parties by officially envisaging an autonomous region in Mindanao, called Bangsamoro. This paper explores the use of exemplars in news media to frame the Bangsamoro framework agreement. Exemplars are single examples used in communication as representatives of a broader phenomenon. This paper utilizes computational tools to mine the large amounts of textual data available from news sources. It applies a critical discourse analysis to online articles covering the Bangsamoro framework agreement by all Qatari and Philippine English-written news outlets. In the Philippine coverage, Bangsamoro is framed utilizing the exemplar of a Muslim other while in the Qatari coverage, Bangsamoro is framed using the exemplar of Muslim victimhood. This may reflect ideologies in the Qatari context that emphasize a solidarity with the Moro minority in the Philippines and ideologies in the Philippine context which reinforce the othering of Muslim Filipinos.
Keywords: Moro Islamic Liberation Front; Bangsamoro; Comprehensive Agreement on the Bangsamoro